A comparative cost analysis of the pathway to diagnosing lymphoma in a tertiary hospital, Western Cape, South Africa - Fareed-Brey, Waarisa (Department of Public Health and Family Medicine, 2023)
Cancer is one of the leading causes of death before the age of 70 in 91 countries (out of 172) with a noted increasing incidence of cancer and mortality (Bray et al., 2018). In tuberculosis (TB) endemic areas, a fine needle aspirate (FNA) is often used as the diagnostic tool of choice when trying to understand the underlying cause of lymphadenopathy (LAP), which can lead to delayed diagnosis of lymphoma (Antel et al., 2019). A significant gap exists in the lack of costing of the diagnostic pathway to diagnosing lymphoma. The study aimed to cost the diagnostic pathways, namely FNA, core-needle biopsy (CNB), and surgical excision biopsy (SEB) using secondary data collected in 2018 (February until October) at Groote Schuur Hospital (GSH), within the tertiary level hospital outpatient clinics to informed the patient pathways. The overall purpose of the study was to inform policy-making decisions and process guidelines. A cost analysis study was conducted using a combination of ingredients-based costing and top-down costing from a provider's perspective. Annual costs were calculated and inflated to 2021 South African Rands using the consumer price index (CPI) and converted to United States American Dollars. More CNBs are currently being performed than SEBs at GSH, and when pathways were followed, CNB initiated pathways (US $567) were less costly compared to FNA initiated pathways (US$ 877). The cost of the CNB procedure varied with the use of a single-use biopsy gun and the multi-use Magnum BARD gun. CNB provides an alternate choice to SEB and based on the study conducted, CNB pathways are less costly. The main cost driver for all three procedures was personnel and this could be decreased by task shifting and training of medical officers and interns.